Policy of the Federal Republic of Germany toward Russia in the multipolar world order: its objectives, tasks and consequences for Europe (Economic and Political Thought, 2017)
The article aims to analyse the FRG’s policy toward Russia at the turn ofthe century and to present its significance to Europe and the developmentof a new global order. Moreover, the author tries to answer many questionsconcerning premises of cooperation between Russia and Germany as well asthe threats they pose to European and world peace and security, inter alia,whether there will not be another Rapallo and whether Russia and Germanywill not try to play a dominant role in Europe. The main thesis of the paperis an assumption that a way to a new, probably multipolar global order is verylong and that Germany, remembering its history and tragic experiences, willnot return to its policy of cooperation with Russia, which aims to take controlover Europe and divide it again. On the other hand, the author writes, cooperationbetween Germany and Russia is indispensible for the stabilisation ofthe situation in Europe and the development of a new democratic order inthe world.